Критическая теория и аутентичная альтернатива репрессивной социальности - Голованов, Борис Дмитриевич; Фролова, Ольга Владимировна (Національний юридичний університет ім. Ярослава Мудрого, 2018)
В статье рассматривается проблема реализации человеческой индивидуальности в условиях постоянного давления социальной системы на сознание и психику людей. Эта проблема исследовалась начиная с 30-х гг. ХХ в. в рамках критической социальной теории (М. Хоркхаймер, Т. Адорно, Г. Маркузе, Э. Фромм и др.). Авторы полагают, что отсутствие позитивного решения названной проблемы в ХХI в. связано с тем, что давление на сознание и психику людей осуществляется современной наукой, которая во многом отреклась от своего первоначального, гуманистического содержания. В условиях ослабления позиций глобальных идеологий наука взяла на себя функции социального контроля. Повсеместное распространение технологического, компьютерного мышления лишает человека способности рефлексии и самопознания.

The irrationality of modern society, divided into separate streamlined fragments of everyday life, became invisible to the individual. Doubts and emotional protest of unreasonableness set by government laws and regulations the most subtle ways are pushed to the periphery of individual and social consciousness. In each case, irrational declared doubt the individual consciousness, whereas the decisions taken at the level of society as a whole look quite rational and sanctified by the authority of science. Мodern science loses its critical evaluation in relation to the social whole created on its basis and becomes a universal ideology of industrial civilization. The rationality of modern scientific technology securely inscribed in the irrationality of society as a whole.Science replaces the weakening of global ideologies in the system of social control, progressive pathos of the past is replaced by attitudes of society of mass consumption. Technological thinking, which dominates in the developed industrial society, establishes a new, more effective forms of social control over individuals. One of these forms is the blurring of the distinction between false and true needs of individuals. «Pseudopatient» in a large quantity are imposed on the individual through sophisticated technology intervention in the sphere of the unconscious.In these circumstances, the categories of psychology and psychiatry become categories of social forces and political processes that support oppressive pressure on individuals. To block the natural resistance of the individuals excessive repression, science begins the attack on the last refuge of their freedom, the inner world of individuals. Repressive civilization deprives the individual the ability to cultivate reflective thinking and to move along the path of self-discovery. Instead of the inner creative space of the individual by external pressure is continuously imposed on the ersatz identity, substituting its authenticity. A variety of collective rituals, widely practised in a civilized society, aimed at maintaining modern myths and the weakening of the critical abilities of the individual to resist the hypnotic influence of the new civil religion.
Critical theory and authentic alternative of repressive sociality
Keywords: идентичность; идеология; технологическая рациональность; атрофия разума; identity; authenticity; ideology; repressive social; technological rationality